Determinants of The Quality of Ongoing Professional Training in an Online Format from The User's Perception: An Empirical Study in Chile - Uribe, Jessica (Journal of Technical Education and Training, 2025)
Continuous training is essential for organizational sustainability, as competency development directly influences productivity and adaptability. This study evaluates the satisfaction perceptions of 999 participants in synchronous online courses, considering variables such as age, work experience, and prior knowledge. Using Stufflebeam’s CIPP model (Context, Input, Process, Product), the most valued aspects of the training program were systematically analyzed. Results indicate high overall satisfaction, particularly regarding technical support, instructor quality, and content relevance. Significant correlations were found between prior knowledge and satisfaction, but not with age or gender. Key areas for improvement include clarity of explanations and pedagogical interaction. It is recommended to adopt differentiated strategies based on participant profiles and to enhance real-time feedback mechanisms. This approach enables training programs to align more effectively with learners’ actual needs, promoting workplace knowledge transfer.